Eficiencia y productividad en el deporte como indicador de desarrollo territorial: El caso de las CCAA espa\~nolas (2011-2018); Efficiency and productivity in sport as an indicator of territorial development: the case of the Spanish Autonomous Communities (2011-2018) - Francisco Antonio García Márquez; María del Carmen Pérez-González; Francisco Javier Maza Ávila (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– This article analyzes the relationship between sport and territorial development. From a Data envelopment analysis (DEA), the Malmquist index and a Tobit regression model, with the use of investment, competitiveness and sports success variables, we want to delve into the knowledge of this binomial for the specific case of the Spanish Autonomous Communities for 2011, 2015 and 2018, first and last year for which data is available, and an intermediate year. The main results show important territorial differences and specificities in sport in Spain and reinforce the close relationship mentioned above.
Keywords: O10; O18; 330; sport; territorial development; Spain; DEA; Malmquist; Tobit